Multi objective optimisation framework for smart metering in smart grids using multi-objective particle swarm optimisation. (2017) - Bansal, Pooja; Singh, Ajmer
Demand of electricity is increasing day by day. One major consumer of electricity is residential sector. Smart grid offers demand response management to handle such increasing demand. In home energy management system (HEMS), demand response is implemented using smart meters. In this paper, an algorithm is proposed to optimise the demand in home environment and unease level of user is also cared about at the same time. The proposed algorithm is implemented using multi-objective optimisation framework. It is evident from results that cost of electricity is reduced because of optimal demand and on the other hand, unease level of user is within the acceptable limit.